Al-insya’ Atholabi Fi Surat Al-Hujurat (Dirasah Tahliliyah Balaghiyah) - Nadhif Nadhif (Alfaz (Arabic Literatures for Academic Zealots), 2022)
Some students face difficulties in understanding the meaning of the Quran in the form of insya thalabi with various meanings that vary based on the context of the verse, sometimes a verse with a pattern of commands but the meaning is not an order but advice, prayer or instructions etc. The purpose of this study was to determine the pattern of insya thalabi and its meaning in Surat al-Hujurat. The type of this research is library research, the data sources in this research consist of primary sources in the form of al-Qur'an al-karim surah al-hujurat and secondary sources in the form of books related to the research theme such as interpretation books, balagah and dictionaries. The research data were analyzed using Balagah descriptive analysis. The results showed that there were 34 insya thalabi in the letter al-hujurat, 16 in the form of amr, 9 in the form of nahi, two in the form of istifham, 6 in the form of nida and 1 in the form of tamanni. As for the meaning of 34 insya thalabi, it is divided into two kinds, namely the essential meaning and the meaning of balaghi. The meaning of balaghi in insya thalabi letter al-hujurat is al-tahdid, al-nuskhi, al-irsyad, al-khusi, al-tasyji', al-khabar, al-tahdid, al-taqrir, al-inkar, al-tamanni li al-wuqu'.